COMPARATIVE ANALYSIS OF THE MICROBIOTA OF THE REPRODUCTIVE SYSTEM IN WOMEN WITH PRIMARY AND SECONDARY INFERTILITY - Zhuraeva, A.Zh.; Shukurov, F.I.; Jalolova, G.S. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2024)
Background. In recent years, the study of the microbiota of the reproductive system has attracted the attention of scientists due to its important role in maintaining reproductive health. An imbalance in the microbiota can lead to the development of gynecological diseases, negatively affecting fertility. Aim. To conduct a comparative analysis of the microbiota of the reproductive system in women with primary and secondary infertility. Materials and Methods. The study included 130 women: 50 with primary infertility (Group I), 50 with secondary infertility (Group II), and 30 healthy women (control group). Microbiota samples were collected using vaginal and cervical swabs. Microbiota identification was performed using 16S rRNA sequencing with the Illumina MiSeq platform. Statistical data processing was performed using SPSS version 25.0. Results. The duration of infertility was 4.2 ± 1.5 years (Group I) and 5.1 ± 1.7 years (Group II). Comparative analysis showed that the level of Gardnerella vaginalis in women from Group I was 80%, which was significantly higher compared to 30% in Group II and absent in the control group (p < 0.05). The presence of Atopobium vaginae was also higher in Group I (60%) compared to Group II (20%) and absent in the control group (p < 0.05). Relative proportions of Lactobacillus spp. were significantly lower in women with primary infertility (70%) compared to Group II (90%) and the control group (100%) (p < 0.05). Conclusion. The results of the comparative analysis of the microbiota of the reproductive system in women with primary and secondary infertility showed significant differences in the composition of the microbiota compared to the control group. Women with primary infertility are characterized by lower microbiota diversity and higher levels of conditionally pathogenic bacteria. These results highlight the importance of the microbiota in maintaining reproductive health and indicate the need for further research to develop new diagnostic and therapeutic approaches.